A framework for scalable global IP-anycast (GIA). - Katabi, Dina (Computer communication review.)
This paper proposes GIA, a scalable architecture for global IP-anycast. Existing designs for providing IP-anycast must either globally distribute routes to individual anycast groups, or confine each anycast group to a pre-configured topological region. The first approach does not scale because of excessive growth in the routing tables, whereas the second one severely limits the utility of the service. Our design scales by dividing inter-domain anycast routing into two components. The first component builds inexpensive default anycast routes that consume no bandwidth or storage space. The second component, controlled by the edge domains, generates enhanced anycast routes that are customized according to the beneficiary domain's interests. We evaluate the performance of our design using simulation, and prove its practicality by implementing it in the Multi-threaded Routing Toolkit.